De novo assembly and annotation of the whole genomic analysis of Vibrio campbellii RT-1 strain, from infected shrimp: Litopenaeus vannamei. (December 2017) - Thirugnanasambandam, R.; Inbakandan, D.; Abraham, L. Stanley; Kumar, C.; Sundaram, S.M.; Subashni, B.; Vasantharaja, R.; Anantha Kumar, A. Arul; Kirubagaran, R.; Khan, S. Ajmal; Balasubramanian, T.
Abstract: Objectives: This study aimed to sequence the whole genome of Vibrio campbellii RT-1 strain. Methods: V. campbellii strain was isolated from an infected shrimp, Litopenaeus vannamei collected from aquaculture ponds, India (12.1899° N, 79.9249° E). The whole genome sequencing (WGS) was performed using the Illumina Hiseq 2500 platform and assembled de novo using SPAdes and Velvet optimiser. Furthermore, the gene prediction and annotation were performed by a rapid prokaryotic genome tool-Prokka. Results: The genome of V. campbellii RT-1 strain has one circular chromosome with 6327218 bp long. V. campbellii RT-1 strain contains 5787 predicted genes with an average of 45% GC content. A total of 86 known genes associated with pathogenicity were identified and 28 genes were found to be responsible for virulence factors. Furthermore, 1112 unigenes were subjected to Gene Ontology (GO) terms, and 4895 predicted proteins were annotated with Clusters of orthologous (COGs) functional groups. Conclusions: The phylogenetic position of V. campbellii RT-1 strain was established through whole genome sequencing and genomic tools which provides a strong platform to further study on genomic alterations and phenotype of V. campbellii . Highlights: The Vibrio campbellii RT-1 consists of a genome of 6.3 MB size with a GC content of 45%. Annotated 5597 protein-coding genes, 11 rRNAs, 124 tRNAs and 54 miscellaneous RNAs. Six fli genes among 28 virulence factors were found to be associated with flagellar biosynthesis and pathogenesis. Genome analysis data of V. campbellii RT-1 will ameliorate the knowledge of pathogenesis in shrimps.